2015
DOI: 10.1007/s12402-015-0187-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding intentionality in children with attention-deficit/hyperactivity disorder

Abstract: One of the main aspects of theory of mind is intentionality which refers to recognizing other people's intentions in their behaviors. The aim of this study was to investigate intentionality in children with attention-deficit/hyperactivity disorder (ADHD). Thirty children with ADHD were compared to thirty age- and IQ-matched normal children. All participants were assessed using the moving shapes paradigm task which contains one large red and one small blue triangle moving around a black screen. They were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…The task was also selected based on its frequent use in ToM investigation in ASD children and adult populations (21,24,27). A recent study furthermore reported ToM deficits in ADHD children using the same task (35). The task consists of twelve 26-48 s cartoons involving two triangles whose movements express: (1) ToM, e.g., persuading (length = 39.0±2.2s), (2) Goal-directed (GD) interaction, e.g., following (length = 39.5 ± 9.5 s), and (3) Random (RD) purposeless motions, e.g., floating (length = 39.8 ± 1.5 s) (71).…”
Section: The Frith-happé Animated Triangles Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…The task was also selected based on its frequent use in ToM investigation in ASD children and adult populations (21,24,27). A recent study furthermore reported ToM deficits in ADHD children using the same task (35). The task consists of twelve 26-48 s cartoons involving two triangles whose movements express: (1) ToM, e.g., persuading (length = 39.0±2.2s), (2) Goal-directed (GD) interaction, e.g., following (length = 39.5 ± 9.5 s), and (3) Random (RD) purposeless motions, e.g., floating (length = 39.8 ± 1.5 s) (71).…”
Section: The Frith-happé Animated Triangles Taskmentioning
confidence: 99%
“…In ADHD, social cognition, and mentalizing deficits are increasingly reported, mostly in children (35)(36)(37)(38)(39) but also in adults (40)(41)(42)(43), albeit not as consistently as in ASD (8). For the adult age group particularly, recent studies have reported intact mentalizing in ADHD, who are instead impaired in empathy and in their ability for generating solutions for social problems (44,45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ToM refers to the ability to represent and understand the mental states of others (Hein and Singer 2008) and one of the main aspects of ToM is understanding the intentions of others (Mohammadzadeh et al 2016). Mohammadzadeh et al (2016) suggest that displays of ASB may be due to the misinterpretation of another's intentions which then lead them to act inappropriately (i.e., aggressively). This may be reflective of a hostile attribution bias (HAB).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous literature, we expected children with behavioural problems to show an impairment in emotion recognition, specifically the recognition of negative emotions. Moreover, given the proposed role of misunderstanding intentions in the development of ASB (Mohammadzadeh et al 2016) we also expected children with behavioural problems to show a specific impairment in understanding intentionality. Given the previously reported relationship between emotion and intention recognition (Skuse 2003) we expected these constructs to be related, and hypothesised that difficulties in emotion and intention recognition would both be associated with severity of behaviour problems.…”
Section: Introductionmentioning
confidence: 99%